Multichannel apparatus for parallel monitoring of light scattering in Dictyostelium discoideum cell suspensions - Daniel F. Lusche; Hanni Rötzer; Rudolf Merz; Hubert Fink; Rupert Mutzel; Christina Schlatterer (BioTechniques, 2004)
Suspensions of Dictyostelium discoideum amoebae display free-running light scattering oscillations at the onset of development. We describe a device to monitor these oscillations in several samples in parallel. The apparatus consists of a thermostated cuvette holder where up to eight cuvettes containing cell suspension are inserted. Cells are aerated and kept in suspension via an airlift. Infrared light emitted from a five-diode array passes through the suspension and is detected by an array of five light detecting diodes. The resulting signal is digitized and recorded with a sampling rate of two measuring points/second. The parallel analysis approach allows determination of the effects of adding of agents or of variations in the external conditions in the same batch of amoebae at the same developmental time point. This represents an advantage over the conventional single cuvette approach, as oscillation characteristics themselves are developmentally regulated. Moreover, as the new experimental setup enables simultaneous analyses of up to eight samples, the behavior of wild-type and several mutant strains can be compared under identical experimental conditions.